EMPLOYMENT ABSORPTION IN MANUFACTURING INDUSTRY: YOGYAKARTA CASE - Aurora Indra Putri (Economic Journal of Emerging Markets, 2010)
Unemployment has been a main problem in economic development, especially in developing countries. Unemployment stems from the inability of the economy to absorb the growing labor force. This paper investigates factors influencing absorbtion of labor in Yogyakarta manufacturing industries. Variables hypothesized to affect the absorbtion are wage, labor productivity, non-wage spending, and output of production. It collects data from Indonesia Centre Bureau of Statistics, and uses panel data regression, namely common effect approach, to estimate the model. Employing Eviews software package, it finds that wage, labor productivity, and output production significantly influence labor absorption. However, non-wage spending does not significantly influence the absorption.Keywords: Labor absorption, wage, labor productivity, non-wage spendingJEL classification numbers: J01, J23, J24